2016
DOI: 10.1155/2016/7591951
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemicals and Medicinal Properties of Indigenous Tropical Fruits with Potential for Commercial Development

Abstract: Hundreds of fruit-bearing trees are native to Southeast Asia, but many of them are considered as indigenous or underutilized. These species can be categorized as indigenous tropical fruits with potential for commercial development and those possible for commercial development. Many of these fruits are considered as underutilized unless the commercialization is being realized despite the fact that they have the developmental potential. This review discusses seven indigenous tropical fruits from 15 species that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
57
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(78 citation statements)
references
References 111 publications
0
57
0
2
Order By: Relevance
“…This power is generated by the phenolic components [17,18]. The Malaka fruit is one of the most widely used fruits as traditional medication with many benefits [19][20][21]. Generally, to obtain phenolic compounds from plant samples, extraction is carried out with different solvent polarities.…”
Section: Introductionmentioning
confidence: 99%
“…This power is generated by the phenolic components [17,18]. The Malaka fruit is one of the most widely used fruits as traditional medication with many benefits [19][20][21]. Generally, to obtain phenolic compounds from plant samples, extraction is carried out with different solvent polarities.…”
Section: Introductionmentioning
confidence: 99%
“…Anacardaceae family which consists of one species of Bouea macrophylla and seven species of the genus Mangifera, is the most studied underutilised fruit in Malaysia. Anacardaceae fruits are mainly used as food source and only some have been reported to possess medicinal properties to treat various ailments such as M. caesia, M. foetida, M. pajang and M. pentandra ( Gerten et al, 2015;Khoo et al, 2016;Mirfat et al, 2016;Mirfat et al, 2015;Salma et al, 2006). Euphorbiaceae, Guttiferae and Sapindaceae are the next commonly studied underutilised fruits in Malaysia.…”
Section: Introductionmentioning
confidence: 99%
“…Parkia speciosa has been used for its diuretic and relaxing properties, treatment of high blood pressure, diabetes and has antibacterial effects on kidney, ureter and urinary bladder (Ko et al, 2014;Salma et al, 2006;Voon and Kueh, 1999) . Meanwhile, A. bilimbi is useful in treating fever, cold, coughs, itches, boils, beriberi, biliousness, inflammation of the rectum, internal haemorrhoids, hypertension, diabetes, syphilis and rheumatism (Khoo et al, 2016;Muhamad et al, 2014;Noor & Noriham, 2014;Salma et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have revealed that consumption of fruit, vegetables, and their byproducts have health benefits against chronic diseases including cardiovascular disease and certain types of cancer 1 . The local fruits of Himachal Pradesh can serve as an ideal source of dietary antioxidants.…”
Section: Introductionmentioning
confidence: 99%